Transcriptome analysis reveals the expression of genes involved in the formation of petal variegation in Impatiens morsei - Hai-Ge Liu; Ting-Ting Feng; Si-Yu Ren; Jian-Yuan Yang; Lu-Qiu Zhao; Xiao-Li Zhang; Mei-Juan Huang; Hai-Quan Huang (Scientific Reports)
Abstract Impatiens morsei is an annual or perennial flower that is a member of the Impatiens genus in the Balsaminaceae family, with pink flowers and dark purple spots on the vexil and wing petals, which is important for the study of new flower colors of Balsaminaceae. However, there has been no study on the flavonoid biosynthesis pathway and carotenoid biosynthesis pathway of I. morsei and the mechanism of its pigment formation is still unclear. Transcriptome sequencing of spotted and non-spotted regions was performed using the petals of I. morsei at full bloom as test material. The results showed that (1) After transcriptome sequencing, 39,917 unigene sequences and 39,110 differentially expressed genes were obtained, and the number of genes that are down-expressed was higher than genes that are up-expressed. (2) Three key genes in the flavonoid biosynthetic pathway, FLS, PAL, and CHS1, were screened out. Additionally, two key genes in the carotenoid biosynthetic pathway, ABA1 and CCS, were identified. Furthermore, two regulatory genes, MSI4 and CPC, were also selected.and analyzed the spatiotemporal expression patterns of these seven genes. The results of this study lay a theoretical foundation for the study of the formation mechanism of floral spots in I. morsei.